2022
DOI: 10.1111/jfbc.14311
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial bioactive peptides from goat Milk proteins: In silico prediction and analysis

Abstract: The main goal of this study was to assess the potential proteins of goat milk (i.e. α‐s1‐casein, α‐s2‐casein, β‐casein, κ‐casein, α‐lactoglobulin and β‐lactalbumin) as precursors of antimicrobial peptides (AMPs). Bioinformatics tools such as BIOPEP‐UWM (enzyme action) were used for the in silico gastrointestinal digestion via a cocktail of pepsin, trypsin, and chymotrypsin A. The antimicrobial activity of peptides was predicted by using four algorithms, including Random Forest, Support Vector Machines, Artific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 61 publications
0
11
0
3
Order By: Relevance
“…The milk‐isolated biologically active peptides play a vital role in human health, but their mechanism of action is still not very clear. Several studies have found that various animal and food sources of BAPs, such as milk and milk proteins, egg, fish, frogs, wheat, meat, and rapeseed, have immunomodulatory (Korhonen, 2009), antihypertensive (García‐Tejedor et al, 2015; Iram et al, 2022; Singh et al, 2020; Solanki & Hati, 2018; Zhang et al, 2020), antioxidant (Panchal et al, 2020, 2021; Toropova et al, 2021), antimicrobial (Abdel‐Hamid et al, 2020; Abdou et al, 2007; Algboory & Muhialdin, 2021; Barroso et al, 2021; Benkerroum et al, 2010; Matin & Otani, 2002; Miao et al, 2016; Rahman et al, 2020; Sansi et al, 2022; Tang et al, 2015; Théolier et al, 2013) and antidiabetic properties (Lafarga et al, 2014). BAPs are mostly derived from casein and whey proteins (Tagliazucchi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The milk‐isolated biologically active peptides play a vital role in human health, but their mechanism of action is still not very clear. Several studies have found that various animal and food sources of BAPs, such as milk and milk proteins, egg, fish, frogs, wheat, meat, and rapeseed, have immunomodulatory (Korhonen, 2009), antihypertensive (García‐Tejedor et al, 2015; Iram et al, 2022; Singh et al, 2020; Solanki & Hati, 2018; Zhang et al, 2020), antioxidant (Panchal et al, 2020, 2021; Toropova et al, 2021), antimicrobial (Abdel‐Hamid et al, 2020; Abdou et al, 2007; Algboory & Muhialdin, 2021; Barroso et al, 2021; Benkerroum et al, 2010; Matin & Otani, 2002; Miao et al, 2016; Rahman et al, 2020; Sansi et al, 2022; Tang et al, 2015; Théolier et al, 2013) and antidiabetic properties (Lafarga et al, 2014). BAPs are mostly derived from casein and whey proteins (Tagliazucchi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The plant proteases displayed more efficiency in releasing ACE‐inhibitory peptides, followed by digestive enzymes and animal proteases. The frequency of release of fragments with ACE‐inhibitory peptides ( A E values 0.0465–0.0668) and number of peptides (Arya et al, 2016; Çağlar et al, 2021; Chen et al, 2021; Duan et al, 2021; Gasteiger et al, 2005; Huang et al, 2022; Li et al, 2020; Minkiewicz et al, 2008; Mooney et al, 2012; Olsen et al, 2020; Samtiya et al, 2021; Sansi et al, 2022; Zhao et al, 2022) by plant proteases was found to be significantly higher than the digestive enzymes ( A E values 0.0162–0.0501; no. of peptides 8–27).…”
Section: Resultsmentioning
confidence: 99%
“…Since the in silico approach speeds up the discovery of bioactive peptides from food proteins, several researchers have used the online tools (such as BLAST, BIOPEP, EXPASy Peptide cutter, PeptideRanker, ToxinPred, etc.) to generate efficient bioactive peptides with potent health benefits (Borawska‐Dziadkiewicz et al, 2021; Duan et al, 2021; Ibrahim et al, 2019; Ji et al, 2019; Pooja et al, 2017; Sansi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular docking is a computational method that can analyze the interaction between molecules (e.g., proteins and peptides) at the atomic level. 113 Sansi et al 114 evaluated 17 AMPs obtained from goat's milk proteins by using in silico gastrointestinal digestion simulation methods and analyzed the 17 AMPs through AutoDock software. The results showed that three of the 17 AMPs displayed substantial antimicrobial activity and could be developed as highly effective antimicrobial drugs in the years to come.…”
Section: Online Toolsmentioning
confidence: 99%